AN EVALUATION OF YELLOW OLEANDER (THEVETIA PERUVIANA) SEED OIL AS A CUTTING LUBRICANT USING THE EXAMPLE OF MEDIUM CARBON STEEL FOR TURNING ON THE LATHE MACHINE - GUMA THOMAS NDYAR; ALHASSAN ABDULLAHI (Journal of Engineering Studies and Research, 2025)
The yellow oleander (YO) is a notable plant of great technological importance. It grows naturally and is grown agriculturally widely and abundantly in Nigeria and many other countries around the globe. The potential of using pure oil extract from YO seed as a more environmentally friendly alternative cutting lubricant to the conventionally and widely used soluble oil was investigated in terms of some basic physicochemical properties, work cooling, and surface finishing performance using, for example, medium-carbon steel as the workpiece in turning on the lathe machine. The kinematic viscosities, pH values, unsaturated oleic acid contents, free fatty acid contents, flash points, pour points, and chloride contents, as well as the cooling and surface finishing capabilities of the steel by the two oils, were experimentally evaluated. The Soxhlet technique was used to extract the YO seed oil. The evaluated kinematic viscosity at 100 oC, pH value, unsaturated oleic acid content, free fatty acid content, flash point, pour point, and chloride content of the YO seed oil through various ASTM and other standard methods were 21.13 cSt, 8.66, 31.23%, 0.91%, 191 oC, 1 oC, and 0.16%, respectively, while the respective values for soluble oil were 19.27 cSt, 6.51, 20.62%, 2.10%, 171 oC, 3.18 oC, and 0%. Comparative analyses of the YO seed oil and soluble oil values indicate a lower ability of YO seed oil to flow than soluble oil, an insignificant corrosivity difference between the two oils, better lubricity of YO seed oil than soluble oil, less tendency of YO seed oil to oxidize and become rancid than soluble oil, less proneness of YO seed oil to fire hazards than soluble oil, better suitability of YO seed oil for cold regions than soluble oil, and higher sterility and tendency towards increased emulsion life of YO seed oil. Turning experiments indicate that the two oils have similar cooling and surface finishing effects on medium-carbon steel. The overall information and analyses suggest that YO seed oil can be extracted sustainably in large quantities in many countries around the world, including Nigeria, and used effectively as a more environmentally friendly alternative lubricant to soluble oil in metal cutting operations such as turning medium-carbon steel on the lathe machine.